Membranes with Chitosan-Chitosan/Phthalate Matrix and Montmorillonite-Carbon Nanotubes Filler for DMFC Applications - Manimoy, Herianus; Botahala, Loth; Mautuka, Zakarias (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
Composite membranes consist of matrix and filler. The matrices used are C and CP. Meanwhile, the filler used is MMT-CNT. The aim of this research is to improve the properties and performance of composite membranes by reviewing the effect of adding montmorillonite particle filler as a matrix and MM-Carbon as a filler. The membrane was made using the phase inversion method and solvent evaporation. The physical characterization carried out was FTIR, XRD, and SEM. Meanwhile, for characterization of membrane performance, namely swelling, methanol uptake, ion exchange capacity, methanol permeability, proton conductivity, and TGA. The results of this characterization showed that the optimum membrane was found at C 1.96 - CP 0.09/ MMT-CNT. In this membrane, methanol permeability was found to be 2.64x10-6 cm2/s, proton conductivity was 3.352x10-6 S/cm, selectivity was 1.2714 Ss/cm3, and membrane stability at a temperature of 290°C. So the optimum composition is C 1.96 grams, CP 0.09 grams, and MMT-CNT 0.129 grams.